Lessons learned from the COVID-19 pandemic: identifying hesitant groups and exploring reasons for vaccination hesitancy, from adolescence to late adulthood - Laure Pauly; Laure Pauly; Laure Pauly; Laure Pauly; Caroline Residori; Hamid Bulut; Dmitry Bulaev; Soumyabrata Ghosh; Marc P. O’Sullivan; Joëlle V. Fritz; Michel Vaillant; Basile Rommes; et al. (Frontiers in Public Health)
IntroductionThe COVID-19 (COronaVIrus Disease-2019) pandemic highlighted the importance of assessing the rationales behind vaccine hesitancy for the containment of pandemics. In this nationwide study, representative of the Luxembourgish population, we identified hesitant groups from adolescence to late adulthood and explored motivations both for and against vaccination.MethodsWe combined data collected via online surveys for the CON-VINCE (COvid-19 National survey for assessing VIral spread by Non-affected CarriErs) study, 1865 respondents aged 18–84, and for the YAC (Young people And Covid-19) study, 3740 respondents aged 12–29. Data from both studies were harmonized and weighted to ensure a sample representative of Luxembourg’s resident population. The surveys included information on demographic and socio-economic factors as well as vaccination hesitancy.ResultsAt the time of the survey, 67.0% of respondents had been vaccinated against SARS-CoV-2 (Severe Acute Respiratory Syndrome COronaVirus-2), while 33.0% of the respondents had not yet been vaccinated. Of those not yet vaccinated, 41.8% of respondents were vaccine hesitant. The most important concerns against vaccination were that the vaccine had not been tested sufficiently (59.4%) and the fear of side effects (52.4%). The most frequent reasons for vaccination were to help society overcome the pandemic (74.8%), and to protect oneself from the consequences of infection with the virus (69.3%). The proportion of unvaccinated respondents unwilling or undecided to get vaccinated was higher in the younger age groups compared to the higher age groups.ConclusionOur findings contribute to improving public health policy communications, not only for future pandemics but also for routine vaccination campaigns. This will help reach those who are unwilling (26.7%) or undecided (15.1%) about vaccination and reinforce strategies that have successfully increased vaccination willingness.